Social comparison of ability and fear of missing out mediate the relationship between subjective well-being and social network site addiction - Steinberger, Philipp; Kim, Hyunji (Frontiers in Psychology, 2023)
As social network sites (SNS) gain more users, the problem of unhealthy user behavior such as SNS addiction arises. We conducted a cross-sectional study (n = 296) on how subjective well-being (SWB) relates to SNS addiction by investigating two possible mediators: social comparison and the fear of missing out (FOMO). While doing so, we tested two distinct associations of social comparison: social comparison of ability (SCA) and social comparison of opinion (SCO). Splitting two components of social comparison is important because, while SCA involves social outcomes often depicted in SNS posts (e.g., performance, material wealth, health, and achievements) that might evoke negative emotions such as FOMO and jealousy, SCO involves presenting or sharing one’s beliefs and values in SNS posts (e.g., arguments, comments, and statements) that might evoke relatively little negative emotions. Our results showed that we replicated previous findings by demonstrating that social comparison and FOMO jointly mediated the relationship between SWB and SNS addiction. More importantly, SCA (together with FOMO), but not SCO, uniquely mediated the relationship between SWB and SNS addiction. Such distinct relations call for future research on identifying specific elements of social comparison contributing to the relation between FOMO and SNS addiction.